Noninvasive evaluation of hepatic fibrosis in patients with hepatitis C using elastography - Hussein Okasha; Mohamed Naguib Abdalla; Nagwa Ramadan; Waleed El-Nabwey (SpringerOpen, 2012)
Background Evaluation of the static elastography as a noninvasive method for predicting liver fibrosis in patients with hepatitis C virus as an alternative modality for liver biopsy. Materials and methodsA group of 35 patients with chronic hepatitis C virus were subjected to biological tests, abdominal ultrasonographic examination, liver biopsy with a histopathological estimation of score of activity and fibrosis, and liver stiffness measurement by means of elastography of the left lobe of the liver. Results Our study showed that there is a significant association between the elastography score and the grade of fibrosis (P=0.001). A significant positive relationship was found between the activity stage and the elastography score (r=0.625 and P=0.01). Elastography has been shown to have a reasonably high sensitivity, specificity, and diagnostic accuracy 100, 48.27, and 57.14% and 87.5, 96.3, and 94.29% for fibrosis grades 0, 1, 2 and 5, 6, respectively. No statistically significant relationship was found between the diameter of the anterior abdominal wall and the accuracy of elastography. However, 63.6% of those with bright liver texture had an incorrect elastography score, whereas 42.9% of those with a normal liver texture had the correct elastography score, and this association was statistically significant (P=0.039). Conclusion Transient elastography indicates whether the liver is normal or cirrhotic; however, it has a low accuracy in the assessment of moderate stages of fibrosis (stages II, III, and IV). Bright liver affects the accuracy of elastography in assessing the degree of fibrosis, whereas anterior abdominal wall diameter does not.